An Analysis of Beliefs about Bhava-Bhũmi Based on Theravada Buddhist Philosophy - (Meekhammasit), Annapiyapha Patesko (Journal of Graduate MCU KhonKaen Campus, 2025)
This research article aims to 1) study the concept of belief in Buddhism, 2) examine the concept of bhava-bhumi in Theravada Buddhist philosophy, and 3) analyze beliefs about bhava-bhumi from the perspective of Theravada Buddhist philosophy. This qualitative study employed documentary research based on the Tipitaka, commentaries, and related academic works. Data were analyzed through content analysis and descriptive synthesis. The findings reveal that 1) in Theravada Buddhism, hell and heaven are grounded in the principles of kamma and samsara, where hell represents the result of unwholesome actions and heaven represents the result of wholesome actions 2) beliefs about bhava-bhumi influence Buddhist ways of life in various aspects, including belief systems, behavior, culture and arts, and political thought 3) philosophical analysis indicates that heaven is not the ultimate goal of Buddhism but merely a conditioned state within samsara, whereas the ultimate goal is liberation through the attainment of Nibbana.